Endocrine Disruption: Computational Perspectives on Human Sex Hormone-Binding Globulin and Phthalate Plasticizers - Sheikh, Ishfaq A.; Turki, Rola F.; Abuzenadah, Adel M.; Damanhouri, Ghazi A.; Beg, Mohd A. (PLOS ONE, 2016)
Phthalates are a class of high volume production chemicals used as plasticizers for household and industrial use. Several members of this chemical family have endocrine disrupting activity. Owing to ubiquitous environmental distribution and exposure of human population at all stages of life, phthalate contamination is a continuous global public health problem. Clinical and experimental studies have indicated that several phthalates are associated with adverse effects on development and function of human and animal systems especially the reproductive system and exposures during pregnancy and early childhood are by far of utmost concern. Sex hormone-binding globulin (SHBG) is a plasma carrier protein that binds androgens and estrogens and represents a potential target for phthalate endocrine disruptor function in the body. In the present study, the binding mechanism of the nine phthalates i.e. DMP, DBP, DIBP, BBP, DNHP, DEHP, DNOP, DINP, DIDP with human SHBG was delineated by molecular docking simulation. Docking complexes of the nine phthalates displayed interactions with 15–31 amino acid residues of SHBG and a commonality of 55–95% interacting residues between natural ligand of SHBG, dihydrotestosterone, and the nine phthalate compounds was observed. The binding affinity values were more negative for long chain phthalates DEHP, DNOP, DINP, and DIDP compared to short chain phthalates such as DMP and DBP. The Dock score and Glide score values were also higher for long chain phthalates compared to short chain phthalates. Hence, overlapping of interacting amino acid residues between phthalate compounds and natural ligand, dihydrotestosterone, suggested potential disrupting activity of phthalates in the endocrine homeostasis function of SHBG, with long chain phthalates expected to be more potent than the short chain phthalates.